PENGARUH KONSELING KELOMPOK TERHADAP PENURUNAN MASALAH HUBUNGAN MUDA-MUDI SISWA KELAS XI IPA SMA NEGERI 2 SIAK HULU T.P 2014/2015 - Susilawati Susilawati '; Raja Arlizon Raja Arlizon; Elni Yakub Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to determine the effect of group counseling services to the decline of the relationship problems young students of class XI IPA SMAN 2 Siak Hulu. The method used is a method of pre-experimental design with one group pretest-posttest design. To collect the data used sample random sampling technique. The subjects were students of class XI IPA SMAN 2 Siak Hulu totaling 30 students. The results showed that before the given service group counseling, relationship problems young people experienced by students in part at the high category and some in middle category, group counseling can reduce relationship problems young people who experienced students, the process of implementation of the counseling group showed change or a decrease in young people relationship problems experienced by students at each meeting, it can be seen from the analysis tcount greater than ttable with significance level of 5% (17.59> 2.000). Thus Ho rejected and Ha accepted, which means there is a significant difference to the decline in young people relationship problems experienced by students before the post given group counseling services. Group counseling services have a positive influence on reducing youth relationship problems experienced by students, can be seen from the results of the test product moment r = 0.46 and r2 = 0.21 kooefesien determination means counseling group influence 21% of the decrease in relationship problems young people who experienced students.Keywords: Counseling Services Group, Adolescent, Young Relationship Problems